(untitled) (Scientific electronic journal "Labor Economics and Human Capital", 2026)
This article explores how the Digital Silk Road agenda aligns with Uzbekistan’s national digital transformation efforts. It focuses on telecom infrastructure upgrades, territorial inclusion, and expanding digital service markets. The study aims to clarify how infrastructure investments connect to service sector growth and inclusive access, while offering practical policy suggestions for ongoing innovation. The methodology includes document and policy analysis, a descriptive-comparative review of official statistics and open data, and a framework mapping the pathway from infrastructure to services, human capital, and institutional trust. Results indicate that improvements in connectivity have boosted online service adoption, increased telecom output, and expanded digital access beyond major cities. However, these advances also pose governance challenges related to competition, cybersecurity, and data management. The article recommends targeted last-mile investments, pro-competition access policies, enhanced cyber and data governance, and digital logistics solutions to promote trade and reduce regional digital disparities.